HBV/HDV co‐infection in the Western Brazilian Amazonia: an intriguing mutation among HDV genotype 3 carriers. Issue 12 (9th July 2014) - Kay, A.; Melo da Silva, E.; Pedreira, H.; Negreiros, S.; Lobato, C.; Braga, W.; Muwonge, R.; Dény, P.; Reis, M.; Zoulim, F.; Trepo, C.; D'Oliveira, A.; et al.
Summary HDV infection still remains a serious public health problem in Amazonia. There are few data regarding the biomolecular aspects of HBV/HDV co‐infection in this region. We studied 92 patients HBsAg+/anti‐HDV IgG+ followed at the Hepatitis Referral Centers of Porto Velho (RO), Rio Branco and Cruzeiro do Sul (AC), Brazil, from March 2006 to March 2007 for whom the HDV and/or the HBV genotype could be determined. The HDV genotype could be determined in 90 patients, while the HBV genotypes could be positively determined in 74. HBV subgenotype F2 is the most prevalent (40.2%), followed by the subgenotypes A1 (15.2%) and D3 (8.7%), while 16.4% were other subgenotypes or genotypes, 4.3% were discordant and 15.2% were unamplifiable. Surprisingly, HDV genotype 3 (HDV‐3) was found in all of the HBV/HDV‐infected patients that could be genotyped for HDV, confirming that HDV‐3 can associate with non‐F HBV genotypes. However, a HDV‐3 mutant was found in 29.3% of patients and was more frequently associated with non‐F HBV genotypes (P < 0.001) than were nonmutant strains, suggesting that the mutation may facilitate association of HDV‐3 with non‐F HBV genotypes.